2006
DOI: 10.1080/09640560500373162
|View full text |Cite
|
Sign up to set email alerts
|

Public Space Management: Present and Potential

Abstract: This paper explores approaches to the management of external public space, both now and in the future. The paper is in five parts. The discussion begins with an exploration of why public space management is universally an important concern by drawing from literature that argues that the quality of public space has declined, and that a greater engagement of the public sector in its management is required. Next, the research methodology is discussed which sought to investigate the management of public space in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 1 publication
0
28
0
Order By: Relevance
“…This can be translated in the creation of clear lines of management and responsibility for public space services at local authority level, or formal agreements linking the performance of, for example, national and regional agencies to the service delivery strategies of local authority departments. In England the effort to better co-ordinate public space interventions has often meant restructuring local authorities to create 'cross-cutting', more strategic structures that can focus on several dimensions of public space and are not limited by the narrower remits of specific services (Carmona and de Magalha˜es 2006). 'Task forces' and working groups that can oversee and harmonise the actions of different agencies have been another common way of securing multi-agency coordination in public space management.…”
Section: The State-centred Modelmentioning
confidence: 99%
“…This can be translated in the creation of clear lines of management and responsibility for public space services at local authority level, or formal agreements linking the performance of, for example, national and regional agencies to the service delivery strategies of local authority departments. In England the effort to better co-ordinate public space interventions has often meant restructuring local authorities to create 'cross-cutting', more strategic structures that can focus on several dimensions of public space and are not limited by the narrower remits of specific services (Carmona and de Magalha˜es 2006). 'Task forces' and working groups that can oversee and harmonise the actions of different agencies have been another common way of securing multi-agency coordination in public space management.…”
Section: The State-centred Modelmentioning
confidence: 99%
“…Decentralization of the decision making process, however, still resided in an operational environment of financial efficiency with the benchmarking of services against performance indicators, tempered by accountability as to its effectiveness, especially in meeting social objectives. Research into the management of public space by Carmona and De Magalhaes (2006) concluded that whilst Best Value has had a positive effect by encouraging a holistic approach to provision, it could not overcome the lack of available funding. As public sector leisure resources have always been finite, some would say scarce (McNamee et al, 2001), whilst having to meet the needs and expectations of many stakeholders, it is inevitable that some needs will be unmet.…”
Section: Introductionmentioning
confidence: 96%
“…Over the past 30 years they have become vandalised, seen as threatening places (Thompson, 2002, p. 61), peripheral to the local community and frequented by marginal groups (e.g., drug users) (Shield, 1991, cited in Aitchinson et al, 2000. Carmona and De Magalhaes (2006) suggest that the general decline in the quality of urban spaces became politically significant at both local and central governmental levels after voters attitudes to this issue became known.…”
Section: Introductionmentioning
confidence: 96%
“…In-between spaces have also been termed 'cracks in the city' and 'lost space' (Loukaitou-Sideris, 1996, Trancik, 1986. Terms like the latter implicitly describe the particular management challenge that spaces in-between represent (Carmona and de Magalhaes, 2006). More specifically, they can be placed in three categories based on the stage of development they relate to: spaces unfit for development; vacant land or land pending development; derelict land.…”
Section: Introductionmentioning
confidence: 99%